The Divestment of PT Semen Gresik (Persero) Tbk.: Evidence and Implications - Irianto, Gugus (Universitas Brawijaya, Indonesia, 2011)
The privatisation of PT Semen Gresik (Persero) Tbk., a state-owned enterprise which operates in the cement industry, had gradually been done. The divestment raised a variety of issues beyond efficiency and financial performance of the company, such as the hegemonic nature of MNCs, justice and fairness, job security, as well as the economic sovereignty. These, in turn, lead to the necessity of developing theoretical perpective which incorporates a variety of aspects in the privatisation enquiry.